The effectiveness of an interactive website based on Differentiated Instruction in developing achievement and awareness of some contemporary jurisprudential issues among middle school students - El-Metarey, Moemina Shabab (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to study the effectiveness of an interactive website based on differential instruction in developing achievement and awareness of some contemporary jurisprudence issues among middle school students. The research sample consisted of (50) female students from the third intermediate grade, and they were divided into two groups: experimental and control; The experimental group studies using an interactive website based on differential instruction, while the control group studies in the usual way, and the quasi-experimental research method was used to achieve the research objectives and prepare its tools, which consisted of: the cognitive achievement test, and the scale of contemporary jurisprudence issues. The finding of the research showed that there were statistically significant differences at the level (0.05) in the post application of the cognitive achievement test and the scale of contemporary jurisprudence issues for the benefit of the experimental group students. Contemporary, and the research ended with providing a set of recommendations and suggestions related to the employment of an interactive website based on Differentiated Instruction in the learning and training environment.